What the literature says about the effects of sanctions on Russia - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
This policy brief frames the discussion of sanctions imposed on Russia since the invasion of Ukraine in a wider international and historical perspective. We present a brief review of recent literature related to the macroeconomic effects of sanctions in Russia and other countries. Our analysis suggests that the general economic effects of the war and sanctions on Russia are neither unprecedented nor insignificant in comparison to previous sanction episodes. The literature also suggests that while the overall economic effects of sanctions on Russia have been diluted by various factors, they have strongly affected the parts of the Russian economy they target.
urn:nbn:fi-fe2023041236162
Keywords: 330; Russia; war; sanctions; trade; FDI